SUATU TINJAUAN UPAYA PENYALURAN DAN PENDAYAGUNAAN TENAGA KERJA PENYANDANG CACAT FISIK DI KOTA SAMARINDA.” - Ince Aldy Mierald Istiawan (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTION               Human resources is one factor that can realize the creation of equitable growth. The economy of a country in particular regions will be said to advance the views from the income that can be earned by every citizen, every person who has the ability deserves a chance to do a job that they can do, to be able to fulfill their lives and be able to raise the dignity they are, not least for those who have imperfections or Persons with Physical Disabilities.               This study aims to determine the extent to which the work done by the government of Samarinda in the distribution and utilization of manpower physical disabilities in the city of Samarinda and to know the efforts made by the Department of Labor government of Samarinda in troubleshooting the distribution of labor physical disability in Samarinda.               Results showed that the government of Samarinda, especially the Office of Manpower and Transmigration basically been running the business for the channel and empower disabled workers this. This is done through the provision of training and apprenticeship, socialization into the company - the company, the provision of accessibility and independent placements and the establishment of Joint Business Group (KUB), but has not been fully implemented because of the provisions contained in Law No. 13 of 2003 and No. 43 of 2003 have not been properly enforced, especially in the provision of criminal sanctions for companies that do not run the administration of 1% quota for disabled workers, in addition to the government of Samarinda yet have a rule or special wisdom which regulates the distribution and utilization of disabled workers.Samarinda City government needs to give a special regulation (Regulationmayor) for the empowerment and the distribution of labor, especially peoplewith disabilities to the owners of the company have sorting and special attention, that Law No. 13 of 2003 and No. 43 of 2003 can be realized in the city of Samarinda.